2015
DOI: 10.12691/jfnr-3-3-14
|View full text |Cite
|
Sign up to set email alerts
|

Proximate and Mineral Compositions of Dried Cauliflower (Brassica Oleracea L.) Grown In Sindh, Pakistan

Abstract: The study was examined the fresh, cabinet dehydrated and sun-dried cauliflower samples were analyzed for proximate as well as mineral analysis. Proximate analysis was cauliflower samples contained 90.62% moisture, 4.42% carbohydrate, 1.98% protein, 0.23% fat, 2.03% dietary fiber and 0.62% ash. Cabinet dehydration and sun drying substantially decreased moisture content to 9.99% and 13.27, respectively. Proportions of others components were increased, which include carbohydrate (42.44% and 38.37% for cabinet and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 24 publications
5
17
2
Order By: Relevance
“…Thus, fermentation was more efficient in the treatments including cauliflower adding benefits such as increased shelf life due to the low pH. Cauliflower is reported to contain approximately 4.2% carbohydrates, with a high concentration of monosaccharides [18]. Legumes, on the other hand, are well-known for containing high amounts of complex oligosaccharides, a component of dietary fiber that is less available for microbial degradation [19].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, fermentation was more efficient in the treatments including cauliflower adding benefits such as increased shelf life due to the low pH. Cauliflower is reported to contain approximately 4.2% carbohydrates, with a high concentration of monosaccharides [18]. Legumes, on the other hand, are well-known for containing high amounts of complex oligosaccharides, a component of dietary fiber that is less available for microbial degradation [19].…”
Section: Resultsmentioning
confidence: 99%
“…However, the fat content of Kale as observed in this study was lower. According to Baloch et al, 2015, the fat content in Brassica oleracea was also found to be 2.16g/100g which was lower value than other vegetables such as cauliflower and Broccoli. The crude fiber and crude protein content were found to be high in Brassica oleraceae 7.8±0.42 and 5.12±0.43 (g/100g) respectively when compared to S. oleraceae.…”
Section: Resultsmentioning
confidence: 99%
“…Cauliflower has many advantages, being a good source of dietary fiber, and dehydration was effective not only in preserving the chemical composition of cauliflower but in also preventing deterioration by reducing moisture. Additionally, cauliflower with low fat could be used in a low caloric diet to reduce weight (Baloch, et al, 2015).…”
Section: Chemical Composition Of Raw and Treated Cauliflower Stemsmentioning
confidence: 99%